The first complete mitochondrial genome of the tribe Rhingiini (Diptera:Syrphidae) and phylogenetic analysis - Zhao Le; Li Gang (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of Ferdinandea cuprea was assembled and annotated applying next generation sequencing, which is the first reported mitogenome reference of species from Rhingiini tribe of Syrphidae family. The mitogenome of F. cuprea has length of 15,907 base pair and comprises of 37 genes (13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes) and one putative control region. Most protein-coding genes are initiated with ATN or CAA(COX1), and terminate with TAA. The results of phylogenetic tree reconstruction statistically suggested the monophyly of Syrphinae, but that of Eristalinae is not supported, and shows tribe Rhingiini is closer to Milesiini.